Feeling connected to nature: validation of the connectedness to nature scale in the Italian context - Lovati, Chiara; Manzi, Federico; Di Dio, Cinzia; Massaro, Davide; Gilli, Gabriella; Marchetti, Antonella (Frontiers in Psychology, 2023)
Environmental issues are at the center of the political and cultural debate, representing one of the greatest challenges of our century. Sustainability and pro-environmental conducts are recognized as increasingly urgent to address the decay of ecosystems. To support the acquisition of attitudes that give greater consideration to environmental issues, experiencing a sense of connection with nature has been acknowledged in psychology as a particularly relevant individual component. Among the most commonly used scales in Anglo-Saxon context to analyses this feeling is the Connectedness to Nature Scale (CNS) assessing the emotional and experiential bond between humans and nature. To examine the reliability and validity of this scale in the Italian context, a study including 271 Italian adults (44,3% female; 55% males; Mean age = 34.70; SD = 13.584; age-range = 18-65 years) was conducted to establish evidence supporting the internal consistency of the CNS, as well as its ability to measure convergent, discriminant, and predictive validity. A Confirmatory Factor Analysis showed that CNS in Italian has a single-factor structure as reported in the original version by (Mayer & Frantz, 2004). Furthermore, as expected, positive correlations were observed between the CNS and proenvironmental attitudes and negative correlations with civic moral disengagement. Finally, as assumed, the CNS positively correlated with mental well-being. A broad vision of this study concerns the idea that individuals who have a stronger connection with nature are likely to exhibit reduced tendencies to cause harm to it.